Identification of therapeutics that target eEF1A2 and upregulate utrophin A translation in dystrophic muscles - Christine Péladeau (Nature Portfolio, 2020)
One potential approach for the treatment of Duchenne muscular dysrophy is to increase expression of the dystrophin homolog utrophin. Here, the authors show that eEF1A2 regulates utrophin expression, and show that 2 FDA-approved drugs upregulate eEIF1A2 and utrophin level in mice, leading to improvement of the dystrophic phenotype.